PRIMARY TEACHERS’ CHALLENGES IN IMPLEMENTING INCLUSIVE EDUCATION IN SCHOOLS OF MALDIVES (Proceedings of International Conference on Special Education, 2022)
This study explored the challenges faced by regular and SEN teachers in implementing inclusive education in government primary schools in Republic of Maldives. The instruments used in this mixed method research is a survey questionnaire and interviews. A survey questionnaire of three sections with an open-ended question on teachers’ challenges were administered to randomly selected regular teachers (N=125) and SEN teachers (N=34). A semi- structured interview guide was used for regular teachers (N= 8) and SEN teachers (N=7). The data from the open-ended question was analyzed for categories and the interview transcripts were thematically analyzed and coded. The top five challenges of RTs in implementing inclusive education in mainstream schools of Maldives were lack of resources, class size, lack of time, lack of trained teachers and lack of knowledge. The top five challenges experienced by STs in implementing inclusive education in mainstream schools of Maldives were lack of resources, lack of trained teachers, teacher attitudes, lack of collaboration and lack of time. It is recommended for policy makers to provide necessary resources, bring changes to current policy of teacher allocation, provide general teachers with skills and knowledge through programs and conduct awareness programs to foster positive attitudes. It is proposed for policy makers to build partnerships with higher education institutions to develop innovative teacher education programs in preparing skilled teachers for implementing inclusive education in Republic of Maldives.